A method for preparing sodium ferric sulfate, a positive electrode material for sodium ion batteries, using titanium dioxide byproducts

By combining titanium dioxide by-products with sodium and carbon sources, a high-value sodium ferrosulfate positive electrode material was prepared, which solved the problem of waste of resources and high production costs of sodium ion battery positive electrode material, and achieved high efficiency and low Costly, the preparation of sodium ferrosulfate and the electrochemical performance improvement.

CN117303449BActive Publication Date: 2024-12-20CHINA THREE GORGES UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311116209.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2024-12-20
Estimated Expiration
2043-08-31

AI Technical Summary

Technical Problem

The existing preparation method for sodium ferric sulfate of the positive electrode material of sodium ion battery does not utilize titanium dioxide by-products, resulting in waste of resources and high production costs, and lacks high-value recycling technology.

Method used

The titanium dioxide by-product is combined with sodium and carbon sources, and the sodium sulfate positive electrode material is prepared by deionized water dissolution, filtration, ball milling and heat treatment. The elements such as Mg, Mn, Ti and other elements in the titanium dioxide by-product are used as heterogeneous. Atomic doping improves electrochemical performance.

Benefits of technology

It realizes the high-value recycling and utilization of titanium dioxide by-products, and prepares sodium iron sulfate positive electrode material with high working voltage and stability, which is suitable for large-scale industrial production, reduces production costs and improves the electrochemical performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117303449B_ABST
    Figure CN117303449B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing sodium ferric sulfate, a positive electrode material for sodium ion batteries, by using titanium dioxide byproducts. The titanium dioxide byproducts are fully dissolved in deionized water and filtered; then, a certain amount of impurity remover is added to the filtrate, stirred, filtered, and dried; then, sodium sulfate, impurity-removed titanium dioxide byproducts, and a certain amount of polyvinyl pyrrolidone are mixed and ball-milled, and anhydrous ethanol is added as a dispersant; dried; finally, the obtained precursor is pre-burned in a nitrogen atmosphere at 200°C and then heated to 350°C for further heat treatment to obtain the sodium ferric sulfate positive electrode material. The preparation process is simple, energy consumption is low, and there is no toxic gas, liquid, or solid emission, which is green and environmentally friendly. The sodium ion battery assembled with the material has high voltage and good cycle performance, which can fully meet the requirements of energy storage devices and low-speed electric vehicles for sodium ion battery positive electrode materials, and greatly reduces the production cost, realizing the high-value recycling of titanium dioxide byproducts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing sodium ferric sulfate, a positive electrode material of a sodium ion battery, by utilizing titanium dioxide byproducts, and belongs to the field of preparation of new materials for sodium ion batteries. Background Art

[0002] The research on sodium-ion batteries is almost synchronized with that of lithium-ion batteries, but it is in a state of stagnation due to its large performance difference with lithium-ion batteries. After 2010, with the rapid application of lithium-ion batteries in the three major fields of consumption, power and energy storage, major lithium-ion battery manufacturers have continuously expanded their production capacity, resulting in tight demand for lithium resources and a sharp rise in prices. Sodium-ion batteries have re-entered people's field of vision. Sodium resources are abundant and widely distributed. The development of sodium-ion batteries can avoid the problem of "stuck neck" resources in the process of industrial development. Although the energy density of sodium-ion batteries (100~150Wh / kg) is lower than that of lithium-ion batteries (120~200Wh / kg for lithium iron phosphate batteries and 200~300Wh / kg for ternary lithium-ion batteries), it is much higher than that of lead-acid batteries (35~50Wh / kg); and the cycle life of sodium-ion batteries (>3000 times) is also much better than that of lead-acid batteries (300~1000 times). In addition, sodium-ion batteries also have the advantages of high safety, excellent high and low temperature performance (working temperature range is -40℃~80℃), and outstanding fast charging performance. In addition, sodium-ion batteries and lithium-ion batteries have similar production processes, high equipment compatibility, and convenient production line conversion. In energy storage applications, cost and life are more important indicators than energy density. Therefore, sodium-ion batteries have greater market competitive advantages than lithium-ion batteries.

[0003] The cathode materials for sodium-ion batteries with application prospects mainly include layered transition metal oxides, polyanionic compounds and Prussian blue compounds. Among them, polyanionic compounds have attracted much attention due to their outstanding advantages such as high working voltage, good stability and high safety. In 2014, P. Barpanda et al. first reported that Na2Fe2(SO4)3 can be used as a high-voltage cathode material for sodium-ion batteries. In particular, its outstanding cost advantage and non-toxic properties have attracted great attention from the industry. my country is a major producer of titanium dioxide. At present, most companies use the sulfuric acid process to produce titanium dioxide. This process produces about 4 tons of byproduct ferrous sulfate for every ton of titanium dioxide produced. With the soaring prices of upstream raw materials for lithium-ion batteries, the preparation of iron phosphate, a precursor of lithium iron phosphate, a cathode material for lithium-ion batteries, using titanium dioxide byproducts as iron sources has become a research hotspot. However, to date, there are no relevant literature and patents on the use of titanium dioxide byproducts to prepare sodium iron sulfate, a cathode material for sodium-ion batteries. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing sodium ion battery sodium ferric sulfate, a positive electrode material of a sodium ion battery, by utilizing titanium dioxide byproducts. The method has a simple process flow and low production cost, and at the same time realizes high-value recycling of titanium dioxide byproducts.

[0005] The preparation method of sodium ferric sulfate described in the present invention is to use titanium dioxide byproduct and sodium source as reactants, and add an appropriate amount of impurity remover. Among them, the sodium source is at least one of sodium sulfate, sodium carbonate, sodium chloride, sodium hydroxide, sodium acetate, sodium oxalate, sodium nitrate, etc. The carbon source is at least one of polyvinyl pyrrolidone, ascorbic acid, glucose, sucrose, citric acid, polyaniline, graphene, reduced graphene oxide, carbon nanotubes, etc. The impurity remover used when pre-removing impurities from titanium dioxide byproducts is sodium sulfide, ammonia water, sodium hydroxide, etc. The main component of titanium dioxide byproducts is ferrous sulfate, which can be used as an iron source. At the same time, the titanium dioxide byproducts also contain a small amount of Mg, Mn, Ti and other elements, which can be used as heterogeneous atoms doped inside the lattice of sodium ferric sulfate positive electrode materials during preparation to further improve the electrochemical properties of the material.

[0006] A method for preparing sodium ferric sulfate, a positive electrode material for a sodium ion battery, by using titanium dioxide byproducts, comprises the following steps:

[0007] S1. After the titanium dioxide byproduct is fully dissolved in deionized water, filtered and dried, a water-washed titanium dioxide byproduct is obtained; the water-washed titanium dioxide byproduct contains 80-90% ferrous sulfate, 0.5-1.5% Mg, 0.1-0.3% Mn and 0.1-0.3% Ti. It inevitably contains a small amount of calcium, sodium, zinc, aluminum, cobalt, lead, potassium and phosphorus.

[0008] S2. The by-product of washed titanium dioxide, a sodium source, a certain amount of carbon source and a dispersant are mixed and ball-milled for a period of time; then dried at a certain temperature; finally, the precursor obtained above is heat-treated in an inert atmosphere for a period of time to obtain a sodium iron sulfate Na2Fe(SO4)2 positive electrode material.

[0009] Preferably, the titanium dioxide by-product is dissolved in water and filtered, and then an impurity remover is added to the filtrate. After filtering and drying, the impurity-removed titanium dioxide by-product is obtained. The impurity remover is sodium sulfide, ammonia water, or sodium hydroxide, and the added amount is 0.3-10% of the mass of the titanium dioxide by-product.

[0010] Preferably, in step S2, the sodium source is at least one of sodium sulfate, sodium carbonate, sodium chloride, sodium hydroxide, sodium acetate, sodium oxalate, sodium nitrate, etc.; the molar mass ratio of the sodium source to the impurity-removing titanium dioxide by-product is 0.95~0.98.

[0011] Preferably, in step S2, the carbon source is at least one of polyvinyl pyrrolidone, ascorbic acid, glucose, sucrose, citric acid, polyaniline, graphene, reduced graphene oxide, carbon nanotubes, etc.; the amount of the carbon source added is 5-20% of the mass of the sodium source and the impurity-removed titanium dioxide by-product.

[0012] Preferably, in step S2, the dispersant added during the ball milling process is at least one of deionized water, anhydrous ethanol, and acetone.

[0013] Preferably, in step S2, the ball milling period is 4 to 10 hours; and the drying at a certain temperature is 55 to 75°C.

[0014] Preferably, in step S2, the heat treatment in an inert atmosphere for a period of time is sintering at 150-200°C in nitrogen or argon for 3-5 h, and then sintering at 300-400°C for 18-32 h; the heating rate is 3-10°C / min.

[0015] The sodium iron sulfate positive electrode material is stirred with acetylene black and polyvinylidene fluoride (PVDF) into a slurry, coated on aluminum foil, and then dried, punched and pressed to form an electrode.

[0016] Compared with the prior art, the present invention has the following significant features:

[0017] (1) The present invention utilizes titanium dioxide byproducts to prepare sodium ferric sulfate, a positive electrode material for sodium ion batteries, during the entire preparation process, no toxic gas, liquid, or solid emissions are emitted, and the process is green and environmentally friendly.

[0018] (2) The raw material cost of the present invention is low, the preparation process is simple, and it is suitable for large-scale industrial production.

[0019] (3) The present invention can make full use of the elements Mg, Mn, Ti and the like in the titanium dioxide byproduct to prepare heterogeneous atom-doped sodium iron sulfate positive electrode material.

[0020] (4) The sodium iron sulfate positive electrode material prepared by the present invention exhibits a working voltage much higher than other sodium ion battery positive electrode materials (sodium nickel iron manganese oxide, Prussian blue materials) and large-scale commercial lithium ion battery lithium iron phosphate positive electrode materials, showing great potential in the application fields of energy storage devices and low-speed electric vehicles.

[0021] (5) The present invention realizes high-value recycling of titanium dioxide by-products. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a comparison chart of the XRD curves of the washed titanium dioxide by-product and the impurity-removed titanium dioxide by-product of Example 1 with the standard card.

[0023] Figure 2This is the XRD spectrum of sodium iron sulfate Na2Fe(SO4)2 / C obtained in Example 1.

[0024] Figure 3 This is the charge and discharge voltage curve of the sodium iron sulfate Na2Fe(SO4)2 / C positive electrode material obtained in Example 1 at a rate of 0.05C in the voltage range of 2.0-4.5V.

[0025] Figure 4 This is a comparison chart of the median voltages of the sodium iron sulfate Na2Fe(SO4)2 / C obtained in Example 1, the positive electrode materials of sodium ion batteries (sodium nickel iron manganese oxide, iron-based Prussian blue), and the positive electrode materials of lithium ion batteries (lithium iron phosphate).

[0026] Figure 5 This is the XRD spectrum of sodium iron sulfate Na2Fe(SO4)2 / C obtained in Example 2.

[0027] Figure 6 This is the charge and discharge voltage curve of the sodium iron sulfate Na2Fe(SO4)2 / C positive electrode material obtained in Example 2 at a rate of 0.05C in the voltage range of 2.0-4.5V. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the embodiments, but the present invention is not limited thereto.

[0029] The titanium dioxide byproduct in the embodiment of the present invention is produced by a sulfuric acid process. This process produces about 4 tons of byproduct ferrous sulfate for every ton of titanium dioxide produced. The titanium dioxide byproduct ferrous sulfate is fully dissolved in deionized water, filtered, and dried three times to obtain a water-washed titanium dioxide byproduct; the water-washed titanium dioxide byproduct is dissolved in deionized water, then an impurity remover is added to remove impurities, filtered, and dried to obtain a cleaned titanium dioxide byproduct.

[0030] Example 1

[0031] After the titanium dioxide by-product is fully dissolved in deionized water, it is filtered and dried to obtain a washed titanium dioxide by-product; deionized water is dissolved in the washed titanium dioxide by-product, and then 10 mL of a 0.64 mol / L sodium sulfide solution is added to remove impurities, filtered, and dried to obtain a cleaned titanium dioxide by-product. The ferrous sulfate content of the cleaned titanium dioxide by-product is 89.64%, the Ti content is 0.003%, and the Na content is 2.995%. Subsequently, 0.7102 g of sodium sulfate, 0.8500 g of the cleaned titanium dioxide by-product, and 0.1560 g of polyvinyl pyrrolidone are mixed and ball-milled for 6 hours, and anhydrous ethanol is used as a dispersant; at 80 o C temperature for about 10 h; finally, the precursor obtained above was heated at 200 oC in a nitrogen atmosphere for 2 h and then heated to 350 o C, and then heat treated for 24 hours to obtain sodium iron sulfate Na2Fe(SO4)2 / C positive electrode material. The preparation process is simple, easy to operate, green and environmentally friendly, and easy to mass produce sodium iron sulfate. Figure 1 This is a comparison chart of the XRD curves of the washed titanium dioxide by-product and the impurity-removed titanium dioxide by-product of Example 1 with the standard card. Figure 2 This is the XRD spectrum of sodium iron sulfate Na2Fe(SO4)2 / C obtained in Example 1. Figure 3 The charge and discharge voltage curve of the sodium iron sulfate Na2Fe(SO4)2 / C positive electrode material obtained in Example 1 at a rate of 0.05C in the voltage range of 2.0-4.5V. It can be seen that its discharge specific capacity can reach 80.8 mAh g -1 The coulombic efficiency can reach 96.2%, and the discharge capacity after 10 cycles is 67.7 mAh g -1 . Figure 4 This is a comparison chart of the median voltages of the sodium iron sulfate obtained in Example 1, the positive electrode material for sodium ion batteries (sodium nickel iron manganese oxide, iron-based Prussian blue), and the positive electrode material for lithium ion batteries (lithium iron phosphate).

[0032] Example 2

[0033] After the titanium dioxide by-product is fully dissolved in deionized water, filtered and dried, the water-washed titanium dioxide by-product is obtained. The ferrous sulfate content of the water-washed titanium dioxide by-product is 86.54%, the Mg content is 0.838%, the Mn content is 0.183%, the Ti content is 0.192%, the Ca content is 0.053%, the Na content is 0.014%, the Zn content is 0.011%, the Al content is 0.004%, the Co content is 0.009%, the Pb content is 0.016%, the K content is 0.001%, and the P content is 0.017%. Then, 0.7102g of sodium sulfate, 0.8500g of the impurity-removed titanium dioxide by-product and 0.1560g of polyvinyl pyrrolidone are mixed and ball-milled for 6h, and anhydrous ethanol is used as a dispersant; at 80 o C temperature for about 10 hours; finally, the precursor obtained above was pre-sintered in a nitrogen atmosphere at 200 ° C for 2 hours and then heated to 350 o C, and then continue heat treatment for 24 hours to obtain sodium iron sulfate Na2Fe(SO4)2 / C positive electrode material. Figure 5 This is the XRD spectrum of sodium iron sulfate Na2Fe(SO4)2 / C obtained in Example 2. Figure 6 The charge and discharge voltage curve of the sodium iron sulfate Na2Fe(SO4)2 / C positive electrode material obtained in Example 2 at a rate of 0.05C in the voltage range of 2.0-4.5V shows that its discharge specific capacity can reach 71.2 mAh g-1 After 10 cycles, the discharge capacity is 66.0 mAh g -1 .

[0034] Example 3

[0035] After the titanium dioxide by-product is fully dissolved in deionized water, filtered and dried to obtain a washed titanium dioxide by-product; deionized water is dissolved in the washed titanium dioxide by-product, and then 1 mL of a 0.64 mol / L sodium sulfide solution is added to remove impurities, filtered, and dried to obtain a cleaned titanium dioxide by-product. The ferrous sulfate content of the cleaned titanium dioxide by-product is 84.38%, the Ti content is 0.178%, and the Na content is 0.262%. Subsequently, 0.7102 g of sodium sulfate, 0.8500 g of the cleaned titanium dioxide by-product, and 0.1560 g of polyvinyl pyrrolidone are mixed and ball-milled for 6 hours, and anhydrous ethanol is used as a dispersant; at 80 o C temperature for about 10 h; finally, the precursor obtained above was heated at 200 o C in a nitrogen atmosphere for 2 h and then heated to 350 o C, and then heat treated for 24 h to obtain the sodium iron sulfate Na2Fe(SO4)2 / C cathode material. The obtained sample has a first discharge capacity of 66.5 mAh g at a rate of 0.05C in the voltage range of 2.0-4.5 V. -1 After 10 cycles, the discharge capacity is 62.1 mAh g -1 .

[0036] Example 4

[0037] After the titanium dioxide by-product is fully dissolved in deionized water, it is filtered and dried to obtain a washed titanium dioxide by-product; deionized water is dissolved in the washed titanium dioxide by-product, and then 10 mL of a 0.64 mol / L sodium sulfide solution is added to remove impurities, filtered, and dried to obtain a cleaned titanium dioxide by-product. The ferrous sulfate content of the cleaned titanium dioxide by-product is 89.64%, the Ti content is 0.003%, and the Na content is 2.995%. Subsequently, 0.7102 g of sodium sulfate, 0.8500 g of the cleaned titanium dioxide by-product, and 0.1560 g of polyvinyl pyrrolidone are mixed and ball-milled for 6 hours, and anhydrous ethanol is used as a dispersant; at 80 o C temperature for about 10 h; finally, the precursor obtained above was heated at 200 o C in a nitrogen atmosphere for 2 h and then heated to 300 oC, and then heat treated for 24 h to obtain the sodium iron sulfate Na2Fe(SO4)2 / C cathode material. The obtained sample has a first discharge capacity of 53.8 mAh g at a voltage range of 2.0-4.5 V at a rate of 0.05C. -1 After 10 cycles, the discharge capacity is 41.1 mAh g -1 .

[0038] Example 5

[0039] After the titanium dioxide by-product is fully dissolved in deionized water, it is filtered and dried to obtain a washed titanium dioxide by-product; deionized water is dissolved in the washed titanium dioxide by-product, and then 10 mL of a 0.64 mol / L sodium sulfide solution is added to remove impurities, filtered, and dried to obtain a cleaned titanium dioxide by-product. The ferrous sulfate content of the cleaned titanium dioxide by-product is 89.64%, the Ti content is 0.003%, and the Na content is 2.995%. Subsequently, 0.7102 g of sodium sulfate, 0.8500 g of the cleaned titanium dioxide by-product, and 0.1560 g of polyvinyl pyrrolidone are mixed and ball-milled for 6 hours, and anhydrous ethanol is used as a dispersant; at 80 o C temperature for about 10 h; finally, the precursor obtained above was heated at 200 o C in a nitrogen atmosphere for 2 h and then heated to 400 o C, and then heat treated for 24 h to obtain the sodium iron sulfate Na2Fe(SO4)2 / C cathode material. The obtained sample has a first discharge capacity of 24.1 mAh g at a rate of 0.05C in the voltage range of 2.0-4.5 V. -1 After 10 cycles, the discharge capacity is 17.3 mAh g -1 .

[0040] Example 6

[0041] After the titanium dioxide by-product is fully dissolved in deionized water, filtered and dried, the washed titanium dioxide by-product is obtained; deionized water is dissolved in the washed titanium dioxide by-product, and then 10 mL of a 0.64 mol / L sodium sulfide solution is added to remove impurities, filtered, and dried to obtain the removed titanium dioxide by-product. The ferrous sulfate content of the removed titanium dioxide by-product is 89.64%, the Ti content is 0.003%, and the Na content is 2.995%. Subsequently, 0.7102 g of sodium sulfate, 1.3901 g of the removed titanium dioxide by-product, and 0.3674 g of ascorbic acid are mixed and ball-milled for 6 hours, and anhydrous ethanol is used as a dispersant; at 80 o C temperature for about 10 h; finally, the precursor obtained above was heated at 200 o C in a nitrogen atmosphere for 2 h and then heated to 350o C, and then heat treated for 24 hours to obtain the sodium iron sulfate Na2Fe(SO4)2 / C cathode material. The obtained sample has a first discharge capacity of 75.9 mAh g at a voltage range of 2.0-4.5 V at a rate of 0.05C. -1 , the Coulomb efficiency is 66.5%.

[0042] Example 7

[0043] After the titanium dioxide by-product is fully dissolved in deionized water, filtered and dried, the washed titanium dioxide by-product is obtained; deionized water is dissolved in the washed titanium dioxide by-product, and then 10 mL of a 0.64 mol / L sodium sulfide solution is added to remove impurities, filtered, and dried to obtain the impurity-removed titanium dioxide by-product. The ferrous sulfate content of the impurity-removed titanium dioxide by-product is 89.64%, the Ti content is 0.003%, and the Na content is 2.995%. Subsequently, 0.7102 g of sodium sulfate, 1.4802 g of the chemical reagent ferrous sulfate heptahydrate, and 0.3674 g of ascorbic acid are mixed and ball-milled for 6 hours, and anhydrous ethanol is used as a dispersant; at 80 o C temperature for about 10 h; finally, the precursor obtained above was heated at 200 o C in a nitrogen atmosphere for 2 h and then heated to 350 o C, and then heat treated for 24 hours to obtain the sodium iron sulfate Na2Fe(SO4)2 / C cathode material. The first discharge capacity of the obtained sample can reach 83.9 mAh g at a rate of 0.05C in the voltage range of 2.0-4.5V. -1 , the Coulomb efficiency is 64.4%.

Claims

1. A method for preparing sodium iron sulfate as a positive electrode material for sodium ion batteries using titanium dioxide byproducts, characterized in that: The following steps are involved: After dissolving the titanium dioxide byproduct in water and filtering, adding an impurity remover to the filtrate, filtering and drying to obtain the impurity-removed titanium dioxide byproduct, wherein the impurity remover is sodium sulfide, ammonia water or sodium hydroxide, and the added amount is 0.3-10% of the mass of the water-washed titanium dioxide byproduct; After washing, the ferrous sulfate content in the titanium dioxide byproduct is 80-90%, the Mg content is 0.5-1.5%, the Mn content is 0.1-0.3%, and the Ti content is 0.1-0.3%. The titanium dioxide byproduct, the sodium source, the carbon source and the dispersant are mixed, ball-milled and then dried to obtain a precursor; The obtained precursor is heat-treated in an inert atmosphere to obtain sodium ferric sulfate, a positive electrode material for a sodium ion battery, wherein heterogeneous atoms are doped inside the lattice of the sodium ferric sulfate Na2Fe(SO4)2 positive electrode material; the heat treatment in an inert atmosphere is sintering at 150-200°C in nitrogen or argon for 3-5 h, and then sintering at 300-400°C for 18-32 h; the heating rate of the heat treatment is 3-10°C min -1 .

2. The method for preparing sodium ferric sulfate as a positive electrode material for sodium ion batteries using titanium dioxide byproducts according to claim 1, characterized in that The sodium source is at least one of sodium sulfate, sodium carbonate, sodium chloride, sodium hydroxide, sodium acetate, sodium oxalate and sodium nitrate; the molar mass ratio of the sodium source to the impurity-removing titanium dioxide by-product is 0.95-0.

98.

3. The method for preparing sodium ferric sulfate as a positive electrode material for sodium ion batteries using titanium dioxide byproducts according to claim 1, characterized in that: The carbon source is at least one of polyvinyl pyrrolidone, ascorbic acid, glucose, sucrose, citric acid, polyaniline, graphene, reduced graphene oxide, and carbon nanotubes; the added amount of the carbon source is 5-20% of the mass of the sodium source and the impurity-removed titanium dioxide by-product.

4. The method for preparing sodium ferric sulfate as a positive electrode material for sodium ion batteries using titanium dioxide byproducts according to claim 1, characterized in that: The dispersant added during the ball milling process is at least one of deionized water, anhydrous ethanol, and acetone; the ball milling time is 4 to 10 hours; and the material is dried at 55 to 75° C. after ball milling.

Citation Information

Patent Citations

  • Recycling integrated utilization method of fipronil waste salt and titanium dioxide byproduct ferrous sulfate

    CN111908440A

  • Hydrophobic and oleophylic Na2Fe2 (SO4) 3 / C positive electrode material and preparation method thereof

    CN115050934A

  • Method for preparing carbon-coated sodium ferric sulfate material, carbon-coated sodium ferric sulfate material and battery

    CN116230888A

  • Preparation and application of in-situ carbon-coated sodium ferric sulfate positive electrode material

    CN116443941A

  • Sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN116613288A